Exploring factors influencing the compliance of patients and family carers with infection prevention and control recommendations across Bangladesh, Indonesia, and South Korea - Park, Ji Yeon; Pardosi, Jerico Franciscus; Respati, Titik; Nurhayati, Eka; Islam, Md. Saiful; Chowdhury, Kamal Ibne Amin; Seale, Holly (Frontiers in Public Health, 2022)
Background: Poor compliance with infection prevention and control (IPC) measures has been a longstanding issue globally. To date, healthcare workers (HCWs) have been the primary target for policy and strategy revisions. Recent studies exploring the contributing factors to the spread of COVID-19 across countries in Asia have suggested that the scope of focus should be extended to family carers who provide patient care activities. This study aimed to explore factors affecting patients’ and their family carers’ IPC compliance in hospitals in Bangladesh, Indonesia, and South Korea. Method: A qualitative study incorporating 57 semi-structured interviews was conducted in five tertiary-level hospitals across the three focus countries between July 2019 and February 2020. Interviews were undertaken with: (1) patients, family carers and private carers; and (2) healthcare workers, including nurses, doctors, and hospital managers. Drawing upon the principles of grounded theory, data were inductively analysed using thematic analysis. Results: A total of three main themes and eight subthemes are identified. Key themes focused on the assumptions made by healthcare workers regarding the family/private carers’ level of understanding about IPC and training received; uncertainty and miscommunication regarding the roles of family/private carers; variations in carer knowledge towards IPC and healthcare-associated infections, and the impact of cultural values and social norms. Conclusion: This exploratory study offers novel findings regarding the factors influencing IPC compliance among patients and their family/private carers across various cultural settings, irrespective of resource availability. The role of cultural values and social norms and their impact on IPC compliance must be acknowledged when updating or revising IPC policies and guidelines. .